(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The aim of this paper is to discuss the contemporary possibility of artificially enhancing humans through the lens of ethics. After having introduced human enhancement in general – showing what can be enhance and how it can be done (§1) –, I will focus on the complex distinction between treatment and enhancement (§2) and on the possible problems enhancements can and should face (§3). Focusing on these problems does not imply arguing against the acceptability or desirability of enhancements. I will claim, indeed, that these are crucial issues even advocates of enhancement should deal with.